(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this collaborative work, Dr. Maria Lopez and Dr. Alan Davis explore the intersection of linguistics and values, unveiling axiological problems inherent in contemporary linguistic research. The article delves into the challenges posed by cultural relativism, ethical considerations, and the intricate relationship between language and values, providing illustrative examples to enhance conceptual clarity.